2021
DOI: 10.1080/08912963.2021.1907367
|View full text |Cite
|
Sign up to set email alerts
|

Non-marine tetrapod extinctions solve extinction periodicity mystery

Abstract: Based on their compiled data set of ten extinction episodes (four of which had no known extinction rates), Rampino et al. ( 2020) claimed a 27.5-My period in non-marine-tetrapod extinctions. I reassessed that claim using the Gauss-Vaníček spectral analysis (GVSA), which revealed spectra of extremely low fidelity (mostly << 1) dominated by the Earth's axial precession, without 99%-significant periods, but with hundreds of 95%-significant periods unrelated to the extinctions and the claimed period. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Other workers, however, do recognize this modulation as physically unrealistic and proceed on to examine possible non-orbital causes for its presence, see, e.g., Boulila et al (2012) study of a ~9-My pseudoperiod in Cenozoic carbon isotope record δ13C but who also fail to explain the presence of this pseudoperiod. In a recent example from non-marine tetrapod extinction record (compiled by , insensitive to the ocean-tidal component as the largest systematic noise constituent, Omerbashich (2021b) found that most if not all of the periods claimed in the past as mass-extinction cycles are instead astronomical reflections, of Earth's axial precession primarily, i.e., n•p. A mass-extinctions period of 27.5 My extracted by ibid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other workers, however, do recognize this modulation as physically unrealistic and proceed on to examine possible non-orbital causes for its presence, see, e.g., Boulila et al (2012) study of a ~9-My pseudoperiod in Cenozoic carbon isotope record δ13C but who also fail to explain the presence of this pseudoperiod. In a recent example from non-marine tetrapod extinction record (compiled by , insensitive to the ocean-tidal component as the largest systematic noise constituent, Omerbashich (2021b) found that most if not all of the periods claimed in the past as mass-extinction cycles are instead astronomical reflections, of Earth's axial precession primarily, i.e., n•p. A mass-extinctions period of 27.5 My extracted by ibid.…”
Section: Discussionmentioning
confidence: 99%
“…More of the similarly simple mathematical relations are noticed readily amongst detected periods in paleodata. For example, looking at the nine periods from Table 2 of Omerbashich (2021b), the 33.84146-My period is just the 8.48624-My period quadrupled, or 6.67870-My quintupled, while the 11.93548-My period is simply the 7.95129-My period tripled-halved, etc. As mentioned earlier, these subharmonic relations -doubling, halving, and tripling primarily -represent discrete time translation symmetry characteristic of subharmonic resonant response of rigid multi-body systems to external periodic forcing.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the method went through simplifications into non-rigorous (strictly non-least-squares) formats, such as the Lomb-Scargle technique. GVSA provides total (absolute) accuracy in extracting periods from natural data sets -to the prescribed accuracy of analyzed data themselves (Omerbashich, 2021). Fed raw data, the GVSA outputs spectral peaks with magnitudes in variance percentages (var%) against linear background noise levels.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the method went through simplifications -into non-rigorous (strictly non-least-squares) formats, such as the Lomb-Scargle technique. GVSA provides total accuracy in extracting periods from natural data sets -to the prescribed accuracy of analyzed data themselves (Omerbashich, 2021b). Once fed raw data, the GVSA outputs spectra with spectral magnitudes in variance percentages, var%, or decibels, dB (Pagiatakis, 1999) against linear background noise levels.…”
Section: Methodsmentioning
confidence: 99%